Implementación de un sistema de transferencia de datos, audio y videoconferencia sobre internet 2 utilizando herramienta de software libre, para el quirófano móvil y su conexión con las instalaciones del Área de la Salud Humana de la U.N.L. como un aporte a la telemedicina. - Jiménez Mora, Jorge Patricio (2011)
The quality of human life marks the development of society, in which information and communication technologies have a substantial influence, all these processes are designed to set the path to information society and knowledge, establishing new paradigms Oriented to the creation of an equitable, fair and caring. This research has as its fundamental purpose to allow through the use of TIC's potential tools for data communication, audio and video which will help exchange information and medical care from the operating room travel through the facilities of the Department of Human Health National University of Loja. Among the main points covered in this research, we have the analysis and definition of the infrastructure and applications to be used for the transfer of information, so we have the development and integration of the communication system to connect the phone to the operating room Human Health area, and finally testing the communication system with different users of the same and define policies for the use and operation of the system.